Zasadność braku instytucji nieważności bezwzględnej małżeństwa w polskim prawie rodzinnym - Dzida, Aleksandra (Ius Matrimoniale, 2018)
The presented article deals with the comparison of the institution of annulment of marriage in secular law and the institution of the annulment of marriage in canon law. Attention is drawn to the effects of the use of both institutions on exspouses and the impossibility of declaring marriage invalid in secular law. The aim of the article is to draw attention to the legitimacy of the current legal regulations for the annulment of marriage and the lack of necessity to introduce the institution of annulment of marriage to the order of secular law. The justification for this statement is, among others the concept of a rational legislator. In addition, it was pointed out that there was a lack of legal significance of the consequences and effects of such an amendment of the law. This article is a demand not to introduce changes that may have a negative impact on the current legal order. Regardless of the above reservations, it also shows the need for cooperation between the secular legislator and the legislator of the Roman Catholic Church in creating a transparent law for each recipient.